2023
DOI: 10.1177/00368504221149798
|View full text |Cite
|
Sign up to set email alerts
|

Double-diffusive stagnation point flow over a vertical surface with thermal radiation: Assisting and opposing flows

Abstract: In numerous industrial procedures, the main concern of design engineers is ensuring adequate heat and mass transfer, such as in the heating and cooling practices of solar water heaters, geothermal systems, extrusion of metal, insulation of buildings, electronics, turbines, aerodynamics, electronics, paper manufacturing, and glass fiber production. The unsteady double-diffusive mixed convection flow of boundary layer nanofluids above a vertical region near stagnation point flow is developed and examined here. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The investigation specifically addressed in situations where the plate experiences alterations within its own plane. Islam et al 23 conducted study by taking into account the complex effects of thermal radiation and differentiating between assisting and opposing flows, the investigation focuses on the double-diffusive stagnation point flow over a vertical surface. This study offers important insights into the behavior of the thermal and concentration boundary layers In order to better understand the thermal properties of these intricate fluid dynamics scenarios, a thorough stability analysis by Bakar et al 24 is carried out to examine the behavior of mixed convection nanofluid flow within a permeable porous medium, taking into account the significant effects of radiation and internal heat generation.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation specifically addressed in situations where the plate experiences alterations within its own plane. Islam et al 23 conducted study by taking into account the complex effects of thermal radiation and differentiating between assisting and opposing flows, the investigation focuses on the double-diffusive stagnation point flow over a vertical surface. This study offers important insights into the behavior of the thermal and concentration boundary layers In order to better understand the thermal properties of these intricate fluid dynamics scenarios, a thorough stability analysis by Bakar et al 24 is carried out to examine the behavior of mixed convection nanofluid flow within a permeable porous medium, taking into account the significant effects of radiation and internal heat generation.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to 1987, theoretical work on 'laminar and turbulent mixed convection boundary layer flows' by Gebhart et al [5] may be found. In addition to the works already mentioned, references [6,7] contain other noteworthy publications on mixed convection.…”
Section: Introductionmentioning
confidence: 99%